Polaigraphically Determination of Stability Constants of Mixed Ligand complexes of Cadmium(II) with Pyridine and Some Amino Acids - Verma, Amit; Chauhan, P.K.S.; Paliwal, R.K. (Asian Journal of Chemistry, 2016)
The mixed ligand complexes of pyridine and lysine and metheonine with Cd(II) have been studied polarographically at constant ionic strength, μ = 1.5M (NaNO3) and pH 8.2 at 25.4 ± 0.1°C. The reduction of the complexes at d.m.e. is reversible and diffusion-controlled. Two mixed complexes [Cd(lys)(pyr)]+, and [Cd (lys)2(pyr)] are formed in Cd(II)––lysine-pyridine system with the stability constants log b11 = 5.230 and log b21 = 8.602. Three mixed complexes [Cd(meth)(pyr)]+, [Cd(meth)(pyr)2]+ and [Cd(meth)2(pyr)] are formed in Cd(II)-metheonine-pyridine system with the stability constants log b11 = 5.322, log b12 = 6.518 and log b21 = 9.113 respectively.